Case report: Autoimmune hemolytic anemia caused by warm and cold autoantibodies with complement activation—etiological and therapeutic issues - Turudic, Daniel; Dejanovic Bekic, Sara; Mucavac, Lucija; Pavlovic, Maja; Milosevic, Danko; Bilic, Ernest (Frontiers in Pediatrics, 2023)
Introduction: Mixed warm and cold autoantibodies in autoimmune hemolytic anemia (AIHA) 30 targeting erythrocytes (RBCs) and platelets are scarcely reported. We present a 5-year-old boy with positive both direct (anti-IgG (1+), anti-IgG-C3d (3+), and indirect antiglobulin (Coombs) tests. The RBCs were coated with polyspecific positive, warm IgG autoantibodies alongside activated complement components. Plasma containing IgM class autoantibodies were found in 1:64 titers with a wide temperature range (4-37°C). Platelets were also coated with IgM autoantibodies. Classical and alternative complement pathways were reduced, such as C3, C4, ADAMTS13 metalloprotease activity, factor H antigen, complement factor B antigen, and C1q antigen alongside elevated sC5b-9 terminal complement complex. Hematuria and/or proteinuria, reduced diuresis, or elevated serum creatinine were absent. The kidney ultrasound was normal. A combined recent EBV and CMV infection was found. First-line treatment consisted of intravenous methylprednisolone (4 mg/kg/body weight for first 72 hours (q12 hr), followed by 2 mg/kg body weight for 21 consecutive days with a slow steroid reduction until plasmapheresis. After the limited response to corticosteroid therapy, Rituximab (375 mg/m2) was administered once weekly (5 doses total), with vitamin B9 and B12. These strategies also showed limited (partial) therapeutic benefits. The treatment was switched to plasmapheresis (5 cycles in total) and IVIg (1g/kg/5 days). This combination significantly improved RBC count and platelet levels, and C3 and C4 levels returned to normal. The follow-up of 2.5 years after treatment shows no sign of relapse. In our case, we presumed that complement regulators were sufficient to control complement activation and complement blockade should be reserved only for devastating, life-threatening complement-related multi-organ failure. Conclusion: We believe that EBV and CMV triggered AIHA, thus activating the complement cascade. We used corticosteroids, rituximab, vitamins B9+B12, PLEX, and FFP in treatment. Final remission was achieved with PLEX and FFP, but the additional late effect of B12 Rituximab and the disappearance of long-lived circulating plasma cells cannot be ignored entirely. Complement activation with genetic background should be assessed in at least severe warm/cold hemolytic anemias with autoantibodies.